Baboushka and the three kings : adapted from a Russian folk tale - Robbins, Ruth.; Sanks, Mary Clement; Sidjakov, Nicolas (Oakland, Calif. : Parnassus Press ; Boston : Houghton Mifflin Co., 1988)
An old woman who was too busy to travel with the Wise Men to find the Child now searches endlessly for Him each Christmas season.
"Baboushka, verse by Edith M. Thomas, music by Mary Clement Sanks": p. [26]-[27].
4.0
K-3
CaCaldecott 1961 Medal Winner
Keywords: Folklore -- Russia; Christmas -- Folklore; Folklore -- Russia; Christmas -- Folklore